Hybrid approach to design optimisation: Preserve accuracy, reduce dimensionality - Kamola, Mariusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper proposes a design procedure for the creation of a robust and effective hybrid algorithm, tailored to and capable of carrying out a given design optimisation task. In the course of algorithm creation, a small set of simple optimisation methods is chosen, out of which those performing best will constitute the hybrid algorithm. The simplicity of the method allows implementing ad-hoc modifications if unexpected adverse features of the optimisation problem are found.
Keywords: design optimisation; simulation optimisation; surrogate model; analysis failure